2008
DOI: 10.1007/s00441-008-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

Localization of chondroitin sulfate proteoglycan versican in adult brain with special reference to large projection neurons

Abstract: Versican is a chondroitin sulfate proteoglycan belonging to the lectican family. Versican has two glycosaminoglycan attachment regions, named the GAG alpha and GAG beta domains, which are both regulated by alternative splicing and yield four protein isoforms. We have investigated the expression and localization of versican in the developing and adult brain by using anti-versican GAG alpha and GAG beta antibodies. Western analysis revealed that GAG alpha-reactive isoform was dominant in the adult brain. Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…2E). In accordance with the findings reported previously (Horii-Hayashi et al, 2008), we found versican GAG labeling to be expressed on neurons, as staining often overlapped with -III-tubulin (Fig. 5K, Supplementary Fig.…”
Section: Cspgs Are Differentially Localized In the Cerebral Cortexsupporting
confidence: 92%
See 1 more Smart Citation
“…2E). In accordance with the findings reported previously (Horii-Hayashi et al, 2008), we found versican GAG labeling to be expressed on neurons, as staining often overlapped with -III-tubulin (Fig. 5K, Supplementary Fig.…”
Section: Cspgs Are Differentially Localized In the Cerebral Cortexsupporting
confidence: 92%
“…This antibody particularly detects versican GAG (versican V2 and V0) domain of mouse versican (manufacturer's webpage) and not GAG domain (V1, V3). On the gel, the antibody detects a high molecular weight band at around 400kDa from cerebral cortex homogenate (Horii-Hayashi et al, 2008). Immunofluorescence staining demonstrated that this antibody labels cortical neurons (Horii-Hayashi et al, 2008).…”
Section: Antibody Characterizationmentioning
confidence: 98%
“…Monoclonal antibody 5D5 to versican G3 domain was kindly supplied as ascites fluid by Prof Firoz Rahemtulla, University of Birmingham, Alabama, USA. Rabbit polyclonal antibodies to the GAG-a (amino acids 535-598) and GAG-b (amino acids 1,360-1,439) core protein domains of mouse versican (Horii-Hayashi et al 2008) were purchased from Chemicon Australia through Invitrogen, Sydney, Australia. Anti type I collagen (clone I-8H5), anti type II collagen (clone II-4CII) were purchased from MP Biomedicals, Ohio, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in versican expression and distribution during embryonic development have also been reported in the CNS, where the V1 and V0 isoforms predominate during embryonic development and decrease rapidly at birth (Landolt et al 1995;Milev et al 1998;Schmalfeldt et al 1998;Horii-Hayashi et al 2008). Less is known about versican expression during lung development.…”
Section: Research-article2015mentioning
confidence: 98%
“…The structure of versican is characterized by an approximately 550-kDa core protein consisting of an amino-terminal (G1) hyaluronan binding domain, a carboxy-terminal (G3) domain, and two central chondroitin sulfate glycosaminoglycan attachment domains, the α-GAG and β-GAG domains (Zimmermann and Ruoslahti 1989;Zako et al 1995;Horii-Hayashi et al 2008;Hatano et al 2012). Versican has four different isoforms that differ in the central GAG attachment domain: V0 (contains both α and β GAG domains), V1 (contains only the β domain), V2 (contains only the α domain) and V3 (devoid of both GAG domains) (Zako et al 1995;Gu et al 2007).…”
Section: Introductionmentioning
confidence: 99%